Polymeric Approaches to Reduce Tissue Responses Against Devices Applied for Islet-Cell Encapsulation - Hu, Shuixan; de Vos, Paul (Frontiers in Bioengineering and Biotechnology, 2019)
Immunoisolation of pancreatic islets is a technology in which islets are encapsulated in semipermeable but immunoprotective polymeric membranes. The technology allows for successful transplantation of insulin producing cells in type I diabetes (T1D) in the absence of immunosuppression. Different approaches of immunoisolation are currently investigated. These approaches involve intravascular devices that are connected to the bloodstream and extravascular devices that can be distinguished in micro- and macrocapsules and are usually implanted in the peritoneal cavity or under the skin. The technology has been subject of intense fundamental research in the past decade as it has co-evolved with novel replenishable cell sources for cure of diseases such as T1D that need to be protected for the host immune system. Although the devices have shown significant success in animal models and even some function in human safety studies most technologies still suffer from undesired tissue responses in the host. Here we review the past and current approaches to modulate and reduce tissue responses against extravascular cell-containing micro- and macrocapsules with a focus on rational choices for polymer (combinations). Choices for polymers but also choices for crosslinking agents that induce more stable and biocompatible capsules are discussed. Combining beneficial properties of molecules in diblock polymers or application of these molecules or other anti-biofouling molecules have been reviewed. Emerging are also the principles of polymer brushes that prevent protein and cell-adhesion. Recently also immunomodulating biomaterials that bind to specific immune receptors have entered the field. Several natural and synthetic polymers and even combinations of these polymers have demonstrated significant improvement in outcomes of encapsulated grafts. Adequate polymeric surface properties have been shown to be essential but how the surface should be composed to avoid host responses remains to be identified. Current insight is that optimal biocompatible devices can be created which raises optimism that immunoisolating devices can be created that allows for long term survival of encapsulated replenishable insulin-producing cell sources for treatment of T1D.